Optimization of the operating parameters based on Taguchi method in an SI engine used pure gasoline, ethanol and methanol - SAYIN, CENK (ELSEVIER SCI LTD, 2016)
In this study, Taguchi's design of experiment method and analysis of variance (ANOVA) were applied in order to find optimum operating parameters giving the best engine performance and exhaust emissions with a minimum number of the engine tests in a spark ignition (SI) engine fueled with pure gasoline, ethanol and methanol. For this purpose, the test engine was operated under different compression ratio (CR), engine speed and ignition timing (IT). In addition, the engine performance and regular brake specific exhaust emission values obtained from an optimized engine were compared to those of the baseline engine. According to result, the optimum CR and engine speed value are found to be 9.0 and 2400 rpm for all fuels. While the optimum IT is also 20 degrees crank angle (CA) for alcohol fuels, it is 26 degrees CA in gasoline. As a result of verification experiment, optimization made by reducing (to about 89%) test number with help of Taguchi was achieved within 95% confidence interval. On the other hand, the engine performance and regular brake specific exhaust emission results obtained from optimized engines generally have improved when compared to those of the baseline engine. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Ethanol; Methanol; Compression ratio; Ignition timing; Taguchi; ANOVA; LAMINAR BURNING VELOCITIES; COMBUSTION CHARACTERISTICS; DIESEL-ENGINE; PERFORMANCE; EMISSIONS; AIR; ETHANOL/GASOLINE; INJECTION; MIXTURES; BLEND